A Thin and Broadband Linear-to-Circular Polarizer Based on Grid-Patch Structure for Ku-Band. (13th December 2018) - Hu, Hao-ming; Zhou, Dong-fang; Lei, Xue; Wu, Jun-mo
Abstract : A three-layer circular polarization selective surface operating in Ku-band is proposed in this communication. We design a thin grid-patch structure to achieve linear-to-circular polarization transformation over a wide frequency band. The periodic structure could be analyzed via equivalent circuit model theory. Numerical simulations have been carried out and the prototype structures have been fabricated and experimentally validated. The axial ratio (AR) of the transmitted field remained below 3 dB over the entire bandwidth, and the 3 dB AR bandwidth is approximately 44.6%. The design has a subwavelength thickness of 6 mm (0.28 λ c ). Besides, this design could be also applied to beam scanning antennas because of its capability in condition of large oblique incidence angle (±50 deg).